Sociodemographic Factors in University-Based Dental Care: A Study at the School of Dentistry, University of Costa Rica (2019-2024) - Gómez-Fernández, Adrián (2025)
Equitable access to dental care remains a challenge in Costa Rica. The School of Dentistry at the University of Costa Rica (FODO-UCR) addresses this issue by providing clinical services integrated with academic training, supported by the SMILE digital health record system. To analyze the sociodemographic profile of patients treated at FODO-UCR between 2019 and 2024, based on data recorded in the SMILE System. This was a quantitative, descriptive, and cross-sectional study. Clinical and sociodemographic data from all patients registered in the SMILE System between 2019 and 2024 were analyzed. Descriptive statistics and Chi-square tests were used to assess differences in categorical variables. A total of 25,465 patients received care. The majority were female (58.5 %), aged 18-30 and 31-40, and resided in San José (65.2 %). The primary reason for seeking care was self-initiative (64.3 %). Most patients were Costa Rican and had incomplete primary or secondary education. The study identified consistent patterns of access based on gender, age, and place of origin. These findings can inform institutional strategies aimed at promoting equity and guiding planning efforts in university-based oral healthcare.